Physical characterization of hydrophobin-like proteins from aerial conidia of entomopathogenic fungus (metarhizium anisopliae var.anisopliae) and their role in controlling termite (coptotermes curvignathus) - Kiong, Diana Siaw Boon (2015)
Hydrophobin-like protein (HLP) was found in the aerial conidia of this fungus and play a role in attachment on the cuticle surface of the termite during pathogenesis. The aim of this study was to isolate and physically characterized HLP from the aerial conidia of two local isolates of M. anisopliae, also to evaluate the interaction effect between HLP and M. anisopliae conidia suspension on the mortality of C. curvignathus. The protein samples were isolated based on their insolubility in hot sodium dodecyl sulfate (SDS). The SDS-insoluble proteins were then purified by three purification methods namely formic acid only, formic acid followed by performic acid, and trifluoroacetic acid. The isolated and purified protein samples were further quantified and characterized as HLP by studying the contact angle when applied on the hydrophobic surface, wetting ability when applied on hydrophilic surface and emulsifying properties. Virulence test of termite bioassay was performed. The HLP samples were verified by their low molecular weight and unique characteristics. Due to the stringent protocol of isolation and purification, the formic acid followed by performic acid purified proteins showed four conspicuous highly intensified bands (13.5 kDa, 15.0 kDa, 16.5 kDa and 17.0 kDa). This method of purification produced highest concentration of HLP (17.82 μg mL-1 and 15.64 μg mL-1 for both isolates TA and LR2, respectively) among the three purification methods. The contact angle measurement showed that both protein isolates HLPTA (58.43° ± 0.25°) and HLPLR2 (57.06°± 0.38°) have the contact angle of < 90°when applied on the hydrophobic surface as compared to the water (108.37° ± 0.50°). When hydrophilic paper was coated with a layer of HLP solution, the paper resisted wetting by water up to 439 ± 20.52 seconds. These results indicated that the HLP is able to convert hydrophilic surface into hydrophobic property and vice versa. This was due to the unique characteristic of HLP which can self-assemble themselves and configure the adsorption at the hydrophobic-hydrophilic interfaces. The HLP also revealed good emulsification effect in the oil-water phase. Aerial conidia of M. anisopliae showed good dispersion in aqueous solution with the application of pre-coated HLP prior to the mixing of conidia suspension. Two application methods were used to test the efficacy and pathogenicity of M. anisopliae with HLP samples. The termite, C. curvignathus showed the fastest trend of mortality (100%) by the pre-coated method with HLPTA prior to the conida topical application on the Day 4. Similar trend of mortality was observed for the same method of application for HLPLR2. HLP treatment alone on termite did not revealed any toxic effect. In conclusion, the most applicable purifying agent used for the purification process of hydrophobin-like proteins (HLP) samples was 98% formic acid followed by perfomic acid. This study showed the strain specificity of the HLP on its application and was found to have enhancing effect but non-toxic when applied alone on C. curvignathus. These unique properties of HLP from local isolates of M. anisopliae var. anisopliae are of great potential to be used in wide range of industrial applications especially in enhancing the formulation of the biological control agent in controlling insect pests.